The Impact of Final Project Workload on the Mental Health of Final-Year Students at Palangka Raya University (UPR) - Yohanes Aditya Pratama; Christiano Jagero Pratama; Fitriana Selvia; Peronika Simanjuntak (Madani: Jurnal Ilmiah Multidisiplin, 2026)
In their final semesters, university students often face significant academic pressure, particularly during the process of writing their final assignments or theses. This prolonged pressure can often trigger stressful conditions that negatively impact their psychological well-being. This study aims to examine the effect of final assignment workload on the mental health conditions of final-semester students at the University of Palangka Raya. The research method utilized is a descriptive and causal quantitative approach. Data collection techniques involved structural questionnaires using the Perceived Stress Scale (PSS-10) and Self-Rating Questionnaire (SRQ-20) distributed online via Google Forms to final-semester students. The results of the simple linear regression analysis confirmed that the final assignment process had a significant negative effect on student mental health, characterized by academic burnout, massive anxiety, and mild depressive symptoms caused by extensive revisions and post-graduation anxiety. This study provides a comprehensive overview to serve as an institutional evaluation base for enhancing campus psychological support systems.